Infrared detection of water ingress in a composite laminate crevice based on room temperature evaporation. (July 2015) - Isakov, D.V.
Abstract: A novel approach to detect water ingress along rivets and screws or other discontinuities is demonstrated. The approach is implemented through the generation of local vacuum. Vacuum triggers evaporation of water at room temperature. The evaporation process consumes heat energy from the surroundings, causing decrease in local temperature that can be detected using thermography. Using water droplets of different size it is shown that the measured result is a complex phenomenon that includes: (i) actual water cooling due to evaporation, (ii) heat transfer from the substrate; (iii) dynamically changing evaporation rate; (iv) finite IR absorption length of water. In application to the discontinuities, the method unambiguously allows distinguishing dry screws from screws experiencing water ingress. In the case of the wet screw, water volumes below 10 μL were sufficient to cause a temperature drop of more than 10 °C and the effect to be lasting for tens of seconds. Such changes are easily detectable by IR sensors or cameras. Although the exact estimation of water ingress volume does not seem to be feasible, the method has proven to be reliable and it is several orders of magnitude more sensitive in comparison with results reported in earlier reports.